2019
DOI: 10.1371/journal.pone.0224295
|View full text |Cite
|
Sign up to set email alerts
|

Growth of young HIV-infected and HIV-exposed children in western Kenya: A retrospective chart review

Abstract: IntroductionThe objective of this study was to determine the growth patterns, rates of malnutrition, and factors associated with malnutrition in children born to HIV-infected mothers in western Kenya using data from an electronic medical record system.MethodsThis study was a retrospective chart review of HIV-infected (HIV+) and–exposed (HEU) children (<5 years) using data collected prospectively in the course of routine clinical care and stored in the electronic medical record system in western Kenya between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 42 publications
5
21
1
Order By: Relevance
“…It is important to recognize there may be confounding variables, such as diet, that were not captured as part of this study. However, these results corroborate with other reports of stunting among HIV+ children [33,37,38]. Overall, our results show HIV-exposed infants and children had poorer overall growth regardless of whether they are HIV-or HIV+.…”
Section: Plos Onesupporting
confidence: 93%
“…It is important to recognize there may be confounding variables, such as diet, that were not captured as part of this study. However, these results corroborate with other reports of stunting among HIV+ children [33,37,38]. Overall, our results show HIV-exposed infants and children had poorer overall growth regardless of whether they are HIV-or HIV+.…”
Section: Plos Onesupporting
confidence: 93%
“…51 In our study, HEU infants had a high prevalence of stunting, which increased with age (32%, 43%, and 58% at age 6 weeks, 12 months, and 18 months, respectively) (see Table 2, Supplemental Digital Content, http://links.lww.com/QAI/B643), a finding that has been documented in 3 previous longitudinal cohorts in LMICs. 9,39,43 The prevalence of wasting (5%-13%) and underweight (7%-15%) in our study was similar to other LMIC cohorts. 9,39,43 Likewise, the prevalence of microcephaly in our study was similar to another study in Zimbabwe.…”
Section: Discussionsupporting
confidence: 87%
“…9,39,43 The prevalence of wasting (5%–13%) and underweight (7%–15%) in our study was similar to other LMIC cohorts. 9,39,43 Likewise, the prevalence of microcephaly in our study was similar to another study in Zimbabwe. 49…”
Section: Discussionsupporting
confidence: 86%
“…While several studies have shown a negative relationship between HIV infected children and attained growth [ 8 10 ], there were no studies, to the best of our knowledge, which studied the relationship between HIV exposure and linear growth velocity. There are concerns that children who are HIV exposed uninfected (HEU) are at risk of deficiencies in multiple micronutrients that play an important role in child growth and development [ 11 ].…”
Section: Introductionmentioning
confidence: 99%